2018
DOI: 10.1111/jcap.12202
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mental health among high school students in Iran: Does mobile phone overuse associate with poor mental health?

Abstract: Planning gender-based health education programs on proper use of MP for students and their parents is suggested to school healthcare providers. The parents should be educated on the proper ways of dealing with their adolescents while using MP at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…In a study on South Korean adolescents (N=1125), cell phone addiction increased the risk of poor sleep quality but not short sleep duration [35]. In a sample of high school students from Iran (N=1034), frequency of daily messages and being awakened at night for mobile phone use were significantly associated with poor mental health, and poor mental health was noted in 63% of the students [36]. In a study on Indonesian students (N=1074), smart phone use at night was entered as an independent variable and sleep disturbance and depressive symptoms as the dependent variables [37].…”
Section: Sleep Disturbancesmentioning
confidence: 98%
“…In a study on South Korean adolescents (N=1125), cell phone addiction increased the risk of poor sleep quality but not short sleep duration [35]. In a sample of high school students from Iran (N=1034), frequency of daily messages and being awakened at night for mobile phone use were significantly associated with poor mental health, and poor mental health was noted in 63% of the students [36]. In a study on Indonesian students (N=1074), smart phone use at night was entered as an independent variable and sleep disturbance and depressive symptoms as the dependent variables [37].…”
Section: Sleep Disturbancesmentioning
confidence: 98%
“…Other sociodemographic characteristics and PSU, such as income, type of residence, and educational level, have yielded mixed results in epidemiological studies. Concerning the association between PSU and education level, four studies reported that PSU was signi cantly associated with education level (23,35,42,44); nine other studies found no relationship between PSU and education level (19,21,25,26,30,33,37,38,45).…”
Section: Psu Measurement Toolsmentioning
confidence: 97%
“…There were several de nitions of smartphone problematic use. According to some authors, it is the inability to limit phone use, which eventually disrupts users' functioning (19,26,29,32,40,47,48). While, other authors claimed that smartphone problematic use was a type of behavioral addiction that included salience, preoccupation, tolerance, withdrawal, and compulsive symptoms (30,33,34,38,41,44,48).…”
Section: Psu De Nitionmentioning
confidence: 99%
“…Rapid advances in memory capacity and speed of smartphones, and constant connectedness to the internet has drastically increased the smartphone usage time (Thomee, ). Given this consideration, as previously addressed by Mortazavi, Mortazavi, and Paknahad (), () mobile phones in modern life are much more frequently used for surfing the Internet than calling.…”
mentioning
confidence: 96%
“…This letter is regarding the paper “Factors associated with mental health among high school students in Iran: Does mobile phone overuse associate with poor mental health?” published in The Journal of Child & Adolescent Psychiatric Nursing (Mahmoodi et al, ). Mahmoodi et al the authors of this paper have investigated the association between mobile phone overuse and mental health in high school students.…”
mentioning
confidence: 99%